Color And COD Degradation of Procion Red Synthetic Dye by Using Fenton-TiO2 Method - Dedi Teguh; Tuty Emilia Agustina; Muhammad Faizal (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
Nowadays, environmental pollution caused by industrial wastewater is quite apprehensive. Most of textile industries used synthetic dyes. Procion red is one of the synthetic dyes that often used in textile industries and classified as a reactive dye that is difficult to decompose in nature and contain harmful toxins. One of the colored wastewater treatment process is by using Fenton reagent and TiO2 catalyst (Fenton-TiO2) as one of Advanced Oxidation Processes (AOPs). The objective of this research is to treat of procion red synthetic dye by using Fenton-TiO2 method and study the effect of procion red concentration, reaction time and the concentrations of TiO2 catalyst on color and COD degradation. In this experiment, the concentrations of procion red were varied between 150-300 ppm, the concentrations of TiO2 catalyst were varied from 0.05 to 0.4% (w/v) and the reaction time of 5 to 20 minutes. The optimum condition was achieved by using procion red concentration of 150 ppm with TiO2 catalyst concentration of 0.4% and reaction time of 20 minutes, which the maximum color and COD degradation of 98.67% and 92% were achieved respectively. This condition was applied to the real wastewater of textile home industry in Palembang. The color and COD degradation of 59% and 44% were found respectively after 220 minutes of reaction.